A LITTLE-KNOWN DOCUMENT ON THE LIFE AND FORMATION OF TUDOR VLADIMIRESCU - Radu Ştefan VERGATTI (Annals: Series on History and Archaeology (Academy of Romanian Scientists), 2021)
This year, 2021, marks the 200th anniversary of the revolution led by Tudor Vladimirescu. It also commemorates two centuries since his assassination. To evoke the formation of Tudor Vladimirescu, I used a little-known document - the moral testament of the master (jupan) Gheorghe Duncea. The act is important because he knew the bailiff Tudor Vladimirescu throughout his life, from childhood to death. This document specified the year of Tudor's birth, the place of birth, the way he learned to read and write, his connection with Horia from Albac, the leader of the Transylvanian peasant uprising of 1784, the reception of the first small boyars ranks, his training as a soldier in the Russian army during the Russo-Turkish war between 1806-1812. Then the Russian generals appreciated him, and the tsar decorated him with the Order of St. Vladimir, gave him a ring and promoted him to the military rank of lieutenant (parucic). After the war, between June and December 1814 he went to Vienna to solve the affairs of the late Elenco Glogoveanu. Then he met the atmosphere of the capital of the Habsburg Empire. His main goal was to fight for the removal of the Greeks from the leadership of Wallachia and eventually Moldova. He arrived in Bucharest again in November 1820. Then he contacted the great boyars who ruled the country. The Greek hospodar of Wallachia Alexandru Suţu was old and ill. On January 15/27, 1821, Alexandru Suţu died. Three of the great boyars, members of the Filiki Eteria, Grigore Brâncoveanu, Ghica, Văcărescu, asked him to start the revolution in Oltenia. Tudor Vladimirescu had been trained for a long time. He left for the north of Oltenia and in four days he reached the great Tismana monastery. From there he summoned his paramilitary force, the Pandurs, and called the people to battle. This is where I must end my communication. There remains only one point that Gheorghe Duncea's will clarifies. He recorded what his nephew, his son-in-law, Captain Bosoancă, told him. He said that being disguised, he went to see what was happening to Tudor Vladimirescu. This is how he saw that Tudor Vladimirescu was seized by a group of the Eteria and taken to the outskirts of Târgoviște. There he was tortured and killed, his stomach was split with a javelin, then ripped out with a suction cup. In memory of the great hero of the Romanian people, a beautiful stone monument was erected on the field from Padeş after the project of the architect State Baloşin.